Pelatihan Ecopreneur Dengan Konsep Saemaul Undong Pada UMKM Desa Waringin Jaya - Bernad Hananto; Wiranta; Iin Masriah; Suhrowardi; Savero RN (JPPI: Jurnal Pengabdian Pelita Insani, 2024)
Ecopreneur developed in this PKM is the development of value-added products from local commodities that are considered no / less economically valuable. The partner group involved is the Non-Governmental Organization group in Waringin Jaya village. The approach taken is the facilitation of the P-IRT permit process and the provision of in-kind support in the form of equipment. In addition, the group is also accompanied in the manufacture of packaging and promotional and marketing media. In this PKM activity, the combination of ecopreneurship and the concept of Saemaul Undong 2.0 is a potential approach to be used in more sustainable community service.